Review of cornea & contact lenses - Bailey, Gretchyn M. ([País no identificado] : Advanced Medical Optics, 2007)
La revista de cornea y lentes de contactos trata sobre la alergia rosácea que es una erupción papular y pustular con forma de acné crónica que involucra el sking de la parte media, la nariz, las mejillas y la frente. Cutaneuserythema e hipertrofia de las glándulas sebáceas especialmente sobre la nariz (rhinohyma) son las características de este proceso de la enfermedad.
INDICE - Allergy and rosacea: connecting the dots new research sheds light on this condition - Understanding corneal marginal infiltrates. Better knowledge can lead to better managment - Safe care in variable wear. Longer-lasting disinfection than hydrogen peroxide - Ferrari or SUV? Make sure your patients perceive your practice the way you do - Sports vision for young patients: addressing compliance concerns - The sweet and the slippery. Glycerin´ns role in ocular lubricants - Claritin: in a class by itself. This widely-prescribed drug jumped from Rx to OTC - Corneal disease consultation. Consultations bring us closer to maximum compensation - Corneal reshaping today and tomorow. The future is bright, especially in managing young progressive myopes - Understanding atopic and vernal keratoconjunctivitis. - The Ortho - K. This modality has a history of ups and downs. - April showers Bring May... Allergies. ocular allergy symptoms can put contact lens wearers over the edge in terms of comfort. Daily disposable lenses offer them a chance to stay spectacle-free and actually enjoy the outdoors - NSAIDS and the peri-operative period. A review fo some recent data adds to our understanding of these medications
Review of cornea & contact lenses, se trabajó por analítica
El artículo está escrito en inglés
Incluye ilustración a colores
Incluye ilustración a color
Incluye conclusión
Incluye bibliografía en cada artículo
Keywords: OPTOMETRÍA -- PUBLICACIONES SERIADAS; ENFERMEDADES DE LOS OJOS -- PUBLICACIONES SERIADAS; OFTALMOLOGÍA -- PUBLICACIONES SERIADAS; SALUD VISUAL -- PUBLICACIONES SERIADAS